Assessment of survey items on social norms relating to sexual behaviour and dating and relationship violence among young adolescents in England: cognitive interviews within two pilot studies. (November 2018) - Meiksin, Rebecca; Ponsford, Ruth; Bonell, Chris
Abstract: Background: Increasingly, interventions that address adolescent sexual and reproductive health and dating and relationship violence (DRV) incorporate social norms approaches to shift perceptions of which behaviours—eg, using condoms or hitting a partner—are typical and acceptable in a reference group of important others. However, evaluations of such programmes rarely measure changes in norms, and there is little consensus on how to do so, particularly for adolescents. We aimed to test survey items measuring attitudes and social norms within two studies piloting interventions to shift norms concerning sexual behaviour, gender-related issues, and DRV. Methods: We asked three secondary schools in Greater London, UK, to select boys and girls aged 12–15 years (appendix ). We explored understandability and answerability via semi-structured cognitive interviews with 21 participants (15 girls, six boys) using a combination of the think-aloud method (in which participants describe their thought processes while responding to survey items) and verbal probes. We conducted thematic analysis, developing cross-cutting themes relating to understandability and answerability of the items tested. Participants provided written informed consent. Ethics approval was obtained from the London School of Hygiene & Tropical Medicine. Findings: Although participants found it easier to answer attitude items about their own views than social norms items about the views of others, our data suggest that respondents could understand both types of survey items and could distinguish between their own views and the views of others in their responses. For norms items, answerability improved when participants could draw on concrete experiences of social norms being publicly displayed—eg, through conversations with friends about their views, or social rewards for boys with many sex partners. Interpretation: Although interventions increasingly aim to shift social norms, a lack of validated survey measures limits researchers' ability to assess normative change among adolescents and test its theorised role in behaviour change. Our data suggest that it is possible to develop measures of norms about sexual behaviour, gender, and DRV that are understandable and answerable by young adolescents in England, but careful consideration is needed to establish the value of including measures of norms that are not publicly manifest among this age group. These findings can inform the development of such measures for future research. Funding: National Institute for Health Research (NIHR) (Public Health Research Board project 15/03/09).